The Positive Relationship of Body Mass Index, Drain Production, and Tumor Necrosis Factor-alpha in Stage IIIB Breast Cancer Patients after Modified Radical Mastectomy - Justinus Dwi Pratjojo Wisnubroto; Ester Hans Sunanto (Biomolecular and Health Science Journal)
Introduction: Modified radical mastectomy (MRM) is one of the treatments for breast cancer (BC). Seroma is a complication that is quite common and can prolong the length of a patient’s stay after MRM which can measure by drain production. Obesity is known to correlate with drain production and the levels of tumor necrosis factor-alpha (TNF-α). However, the study on the relationship between obesity with drain production and TNF-α remains unclear. Methods: This study was an observational analytic design with a cross-sectional approach. Samples consist of third-stage BC patients after MRM in Saiful Anwar Malang Hospital from June 2020 to September 2020. The blood sample will be taken 24 h after MRM and the value of TNF-α will be measured and drain production will be recorded. The statistical analysis using regression test with a significant level of P < 0.05. Results: There were 30 patients in this study with a mean age of 47 ± 4.5 years old. The mean height, weight, and body mass index (BMI) were 59 ± 6.7 kg; 156.90 ± 5.8 cm, and 24.75 ± 4.5 kg/m2, respectively. The most BC type was luminal B (60%). Increasing BMI affects drain production with a contribution of 83%, and 17% from another variable. Increasing BMI also affects TNF-α with a contribution of 45%, and 55% from another variable. Conclusion: BMI is one of the factors that affects positively drain production and TNF-α in overweight patients after mastectomy than normoweight patients.